Effects of home-based cardiac exercise rehabilitation with remote electrocardiogram monitoring in patients with chronic heart failure: a study protocol for a randomised controlled trial. Issue 3 (5th March 2019) - Li, Jiahui; Yang, Peng; Fu, Dongliang; Ye, Xiaojun; Zhang, Lifang; Chen, Gang; Yang, Yiyun; Luo, He; Chen, Li; Shao, Mingjing; Li, Chunyan; Liu, Yi; et al.
Abstract : Introduction: Patients with chronic heart failure (CHF) can benefit from exercise rehabilitation (ER) with significant improvements in exercise capacity, quality of life and reduction in hospitalisations. Despite its reported benefits, only a small number of patients with CHF attend ER due to poor adherence, and improper exercise may even lead to adverse events. Remote ECG monitoring system (REMS) has the potential to overcome these obstacles. We hypothesise that home-based cardiac ER using REMS in CHF patients is effective compared with conventional ER without monitoring. Methods and analysis: This study is a prospective, randomised, parallel controlled clinical trial designed to evaluate the effectiveness of home-based phase-II ER with REMS in the treatment of CHF with a target enrolment of 120 patients (left ventricular ejection fraction <50%, New York Heart Association (NYHA) classes I to III). Patients are randomised to either REMS rehabilitation group or conventional rehabilitation group in a 1:1 ratio. All patients start an exercise training in a supervised setting and then transition to a home-based regimen. The supervised training phase consists of 12 supervised training sessions, three sessions per week for 4 weeks. During the home exercise phase, patients exercise five times per week for 8 weeks. In the REMS group, patients wear monitors during exercise to ensure that exercise intensity is within the set ranges. REMS will also detect risky arrhythmia and alert the patients and their doctors on time. The training intensity is not monitored in the conventional rehabilitation group. The primary outcome is exercise capacity improvement measured by peak oxygen uptake (VO2 peak) (baseline vs 3 m). Secondary outcomes include 6-min walk test, NYHA classes, echocardiographic parameters, cardiac biomarkers, major adverse cardiovascular events, quality of life, psychological well-being and patients' adherence to the rehabilitation programme. Ethics and dissemination: This study was approved by Ethics Committee of China-Japan Friendship Hospital for Clinical Research (No. 2018–55 K39). The results of this study will be disseminated via peer-reviewed publications and presentations at conferences. Trial registration number: ChiCTR-RNR-17012446; Pre-results.